Combined Muscle Biopsy and Comprehensive Electrophysiology in General Anesthesia is Valuable in Diagnosis of Neuromuscular Disease in Children - Hoei-Hansen, Christina E.; Tygesen, Marie L. B.; Dunø, Morten; Vissing, John; Ballegaard, Martin; Born, Alfred P. (Neuropediatrics, 2021)
Aim The diagnostic workup in patients with delayed motor milestones suspected of having either myopathy or a congenital myasthenic syndrome is complex. Our hypothesis was that performance of a muscle biopsy and neurophysiology including stimulated single-fiber electromyography during an anesthetic procedure, combined with genetic testing has a high diagnostic quality.Materials and Methods Clinical and paraclinical data were retrospectively collected from 24 patients aged from 1 month to 10 years (median: 5.2 years).Results Neurophysiology examination was performed in all patients and was abnormal in 11 of 24. No patients had findings suggestive of a myasthenic syndrome. Muscle biopsy was performed in 21 of 24 and was normal in 16. Diagnostic findings included nemaline rods, inclusion bodies, fiber size variability, and type-II fiber atrophy. Genetic testing with either a gene panel or exome sequencing was performed in 18 of 24 patients, with pathogenic variants detected in ACTA1, NEB, SELENON, GRIN2B, SCN8A, and COMP genes.Conclusion Results supporting a neuromuscular abnormality were found in 15 of 24. In six patients (25%), we confirmed a genetic diagnosis and 12 had a clinical neuromuscular diagnosis. The study suggests that combined use of neurophysiology and muscle biopsy in cases where genetic testing does not provide a diagnosis can be useful in children with delayed motor milestones and clinical evidence of a neuromuscular disease.
Keywords: children; diagnostic yield; muscle biopsy; neuromuscular disorders; single fiber electromyography